IDENTIFICATION OF SEAWATER INTRUSION DISTRIBUTION PATTERNS USING 2D ELECTRICAL RESISTIVITY TOMOGRAPHY (ERT) DATA IN SEMARANG, INDONESIA - Minarto, Eko; Utami, Amanda Rizky; Handayani, Lina; Sudrajat, Yayat (Indonesian Physical Review, 2025)
Various environmental problems exist in the northern coast area of Semarang, Indonesia, including land subsidence, tidal flooding, increased chloride content in several monitoring wells, and salinity in resident wells. These issues indicate a decrease in groundwater quality caused by seawater intrusion. Sanitary and health issues have a significant impact on many environmental issues, including decreased soil fertility and building damage. The problem of seawater intrusion can be identified by the geoelectric resistivity method (multi-electrode dipole-dipole configuration). The aim of this research is to detect the presence of seawater intrusion in groundwater zones and determine the extent of its distribution to the mainland. Data collection was carried out along the western canal flood. The data obtained distribution of subsurface apparent resistivity values. Interpretation of the 2D cross-sectional model identified as a seawater intrusion zone with low resistivity (ðœŒ < 3 â„¦ m) ranging from 0-2.600 m. Thick in the northward with a depth of 30-60 m and becomes thin in the south at 2.600 m. At a trajectory 2.600-7.000 m low resistivity is still found in a local spot. The result of the 2D cross-section model inversion shows very good result. Predicted data is quite close to the observed data shown by an average small RMS 2.37% - 4.11%. And shown by a fast convergence curve. The coastal area of Semarang is also found to be made up of five layers: alluvial soft clay, silt clay, sandy clay, granule sand, and coarse sand. These results fit with the well log data around the research area. Estimates of the distribution of seawater intrusion in more detail to the mainland need to be further investigated using other geophysical methods and testing of monitoring wells or resident wells around the research area for more accurate results.